Effectiveness of developing cross-cultural competence of pre-service teachers: a mixed-meta method research - Ailauova, Zhazira; Dogan, Yunus; Batdi, Veli (Routledge Journals, Taylor & Francis Ltd, 2024)
In today's interconnected world, cross-cultural competence is essential for students' success. This article investigates how educational interventions foster this crucial skill. Using a mixed-meta research method, the study combines a meta-analysis of 16 quantitative studies (12,800 participants) with a meta-thematic analysis of 7 qualitative studies. The meta-analysis examines the impact of cross-cultural competence on academic achievement, considering variables like class size, intervention duration, and student levels. The qualitative analysis identifies themes of competence effectiveness, sensitivity, and awareness. Together, these findings highlight the positive impact of targeted interventions on enhancing students' cross-cultural competence, offering valuable insights for educators aiming to prepare students for a globalized society.
Keywords: Cross-cultural competence; cross-culture; intercultural competence; competence; awareness; sensitivity